Construction Of Sexual And Gender Minority Identity Among Malay-muslim Natal Females: A Meta-synthesis - Syed Jaapar SZ; Muhamad R; Abdul Razak A; Bakar Mc; Mokhtar RH (Kulliyyah (Faculty) of Medicine, International Isl, 2024)
Indexed by WOS/Scopus